Best management practices used by companies in Campos Gerais region, Paraná, Brazil - Ditkun, Sérgio; Oshiro, Jackson Luis; Kovaleski, João Luiz; Negri Pagani, Regina; Tadashi Yoshino, Rui (REBRAE, 2016)
In order to maintain its productivity, it is necessary for a company more than technical expertise of its staff; it is also necessary to use the techniques of industrial management, appropriate to achieve organizational goals. This article examines perceptions of students’ faculties in the in the region of Campos Gerais, Paraná, Brazil. They were asked to respond a questionnaire, which would demonstrate the reality of organizations where they work as formal collaborators or interns. The main objective of the research is to identify the use of management practices as tools to improve productivity and, consequently, organizational competitiveness. Through these information and analysis it was possible to make a comparison with the management practices used by companies in the State of Paraná, reported in the Industrial Survey, annually conducted by FIEP (Federation of Industries of Paraná State). The methodological research is characterized as descriptive and exploratory held by a multi-case study with qualitative approach. The survey results indicated that the business scenario in the region of Campos Gerais shows that the analyzed companies mostly do not adopt management practices. However, when considering the analysis by sector, it was observed that the ERP (Enterprise Requirements Planning) is the main technique used in the industrial sector, and in the other sectors the lack of a management technique prevails.